2021
DOI: 10.1111/jfpe.13827
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid infrared with hot air drying of Pisang‐Awak banana: Kinetics and shrinkage quality

Abstract: The purpose of this study was to develop the prototype drying system for drying the Pisang-Awak (PA) banana. It was designed and implemented to study the drying kinetics in each drying mode: hot air drying (HA), infrared drying (IR), and hybrid drying (Hy). The experimental results were fit with simulation results from the finite element method (FEM). Two statistical parameters, the coefficient of determination R 2 and the root mean square error RMSE ð Þ, were used to assess the fit between experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Finite element method (FEM) is a powerful numerical technique that was used to simulate phenomena in food processing such as heat and/or mass transfer, internal stress distribution, as well as chemical and biological processes (Ashtiani et al, 2019; Chiang et al, 2017; Hao et al, 2017; Vishwakarma et al, 2022). FEM also used to simulate the drying process to explore the drying mechanisms for optimizing the design of the drying devices as well as the drying conditions (Kamali et al, 2021; Nachaisin et al, 2016; Puangsuwan et al, 2021; Yazicioglu et al, 2021). The more accurate the simulation parameters are, the more realistic the drying results are obtained by the FEM (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Finite element method (FEM) is a powerful numerical technique that was used to simulate phenomena in food processing such as heat and/or mass transfer, internal stress distribution, as well as chemical and biological processes (Ashtiani et al, 2019; Chiang et al, 2017; Hao et al, 2017; Vishwakarma et al, 2022). FEM also used to simulate the drying process to explore the drying mechanisms for optimizing the design of the drying devices as well as the drying conditions (Kamali et al, 2021; Nachaisin et al, 2016; Puangsuwan et al, 2021; Yazicioglu et al, 2021). The more accurate the simulation parameters are, the more realistic the drying results are obtained by the FEM (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The previous study reported jackfruit drying, where they have considered all the above‐mentioned considerations for the modeling purposes (Tuly et al, 2023). Studies available on the FEM‐based HMT modeling of drying considered material properties as constant (Hashemi & Ranjbar Nedamani, 2022; Puangsuwan et al, 2021). Hence, HMT modeling with the incorporation of variable material properties along with shrinkage studied in the current work will add novelty.…”
Section: Introductionmentioning
confidence: 99%
“…Different physical methods are used to determine the degree of shrinkage in meals. These approaches include taking repeated measurements of the food before and after drying with a ruler or digital caliper and estimating the shrinkage ratio using an average computation (Puangsuwan et al, 2021). Furthermore, one of the most widely used approaches is to calculate the food's shrinkage rate using the principle of displacing the food with water by placing it into metered containers holding water or organic solvent.…”
Section: Introductionmentioning
confidence: 99%